Rota para produção de biodiesel de microalgas - Madeira, Fabiana Alves (Universidade Federal de São Carlos, 2024)
This work presents a possible bench-scale technological pathway for biodiesel production from microalgae. Microalgae are found worldwide and are potential producers of raw material for biodiesel. They are still underexplored for this purpose, but are gaining more incentives and research in this area due to their advantageous characteristics compared to terrestrial oilseed crops, such as high conversion of sunlight to biomass, high efficiency, ability to be cultivated in non-potable water, and rapid and easy growth. In addition, they are photosynthetic microorganisms that fix atmospheric CO2, thereby mitigating the greenhouse effect. For the production of biodiesel, the following main steps are considered: cultivation, biomass harvesting, extraction of lipids present in the cells, and finally transesterification of acylglycerides to essentially biodiesel and glycerol. Lipid extraction has been highlighted as one of the most critical steps, with various possible methods to disrupt the cell wall, including the use of polar and non-polar solvents, mechanical pressing, supercritical fluids, osmotic shock, among others. In the production and extraction of lipids from biomass, it is important to carefully consider the steps and characteristics of the material used, as they may affect the quantification and yield of the final product. The techniques generally have high energy requirements, low environmental sustainability and high processing costs. It is noted that Scenedesmus obliquus has characteristics that make it versatile for different extraction methods; however, in the current case study, the most appropriate extraction technique would be the use of microwave-assisted extraction combined with ethyl acetate solvent. For drying, oven drying is suggested, while for harvesting, centrifugation of the biomass produced in the photobioreactor proved to be more appropriate.
Route to production of biodiesel from microalgae
Keywords: Biodiesel; Microalgae; Scenedesmus obliquus; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA